Evaluation of Bone Health among Type 2 Diabetes Mellitus Patients: An Application of Health Belief Model - Abdulameer, Shaymaa; Sahib , Mohanad; Syed Sulaiman, Syed Azhar (Journal of Pharmacy and Nutrition Sciences, 2021)
Background: Type 2 diabetes mellitus (T2DM) and osteoporosis remain one of the major public health problems worldwide with a considerable burden on society. Health belief toward osteoporosis is fundamental to all osteoporosis management programs and is often a pre-requisite for initiating desired behavioral changes. The aim of this study was to assess: the level of the Malay version of the Osteoporosis Health Belief Scale (OHBS-M) among T2DM patients; the relation of socio-demographic characteristics, clinical data with OHBS-M level and the correlation between OHBS-M score and T-score. Methods: An observational, cross-sectional study design was conducted among T2DM patients. Socio-demographic and clinical data were collected using a convenient sampling method. All T2DM patients underwent the bone mineral density measurement using a quantitative ultrasound scan (QUS). Results: The result showed the average age of the participants was 62.67± 9.24 years. The study findings revealed that the average total score of OHBS-M 143.08±24.22 (median 141.50) with 85.60% of T2DM patients had a low level of osteoporosis health belief. Moreover, a significant correlation was found between the QUS T-scores and osteoporosis health beliefs. Conclusions: The study findings revealed that the assessment of T2DM patients’ bone health and health belief toward osteoporosis is crucial to improve an osteoporosis preventive strategy for high-risk populations.